Exploring Motion Sequence of Virtual Characters: Experimenting Motion Capture Variables - Joon, Jong Sze; Hui, Soon Eu; Rafi, Ahmad (2007)
The purpose of the research is to study the detail of motion of various subjects with differences in physical attributes. The research outlines how different physique produces different behavioural patterns based upon mass and proportion. This research focuses on 'walk motion' to identify the differences in each subject's physical attributes by sampling subjects of physical differences. This experiment employs Vicon8i((R)) Optical Motion Capture system (MOCAP) to study the detail of human motion by extracting the subjects' core motions for analysis with pre-defined actions. The research used the findings to establish the relationship between height and weight against motion frequencies in 3D space.